Diversidade genômica e potencial formicida do óleo essencial de Croton tetradenius Baill - Brito, Fabiany de Andrade (2020)
Croton tetradenius Baill. (Euphorbiaceae), an aromatic and bioactive plant endemic to the Northeast region of Brazil, has insecticide and fungicide potential. Analyzing genetic variability and implementing biological activity are important steps for establishing collections in Active Germplasm Banks for conservation of a plant species. Thus, the objective of the present study was to estimate the genomic diversity and genetic structure of C. tetradenius in Sergipe for introduction of this species in the Active Germplasm Bank of Medicinal and Aromatic Plants of the Federal University of Sergipe (Universidade Federal de Sergipe - UFS), as well as evaluate the toxicity and sublethal effects of essential oils from C. tetradenius genotypes and their major compounds on the leaf-cutting ant Acromyrmex balzani. Genetic analysis was conducted by collecting 38 plants in four cities in the state of Sergipe, Brazil (Porto da Folha, Poço Redondo, Lagarto, and Pacatuba) and using the molecular markers of single-nucleotide polymorphisms (SNP) obtained from genotyping by sequencing (GBS). The essential oils from five C. tetradenius plants from the same locations and their major compounds: 1,8-cineol, α- pinene, camphor, (E)-pinocarveol, and p-cymene, were tested by fumigation on A. balzani worker ants collected from anthills at UFS. The reagent 3% cetyltrimethylammonium bromide (CTAB) was used in extraction of DNA for development of the genomic library, followed by sequencing, processing of the raw sequences, and filtering, resulting in identification of 1387 SNP markers. A low average genetic diversity was observed (HO < HE = 0.086; I = 0.143; f = 0.099). According to the analysis of molecular variance (AMOVA), greater genetic diversity was observed within the localities (95%) than between the localities (5%), and genetic differentiation (FST = 0.041-0.062) among populations was low. The discriminant analysis of principal components (DAPC) showed greater overlap between the Lagarto and Poço Redondo plants, indicating that the current gene flow was less than the historical gene flow. The toxicity of the treatments was evaluated from the concentrations and lethal times. The sublethal effects were obtained through choice and no-choice behavioral bioassays of the leaf-cutting ants. All the treatments repelled A. balzani and affected ant behavior. A. balzani survival declined; the highest LT50 was 42.91 hours for CRT042. LC50 values ranged from 1.47 to 2.40 μL.L-1 for the essential oils and from 0.45 to 11.20 μL.L-1 for the major compounds, camphor being the most toxic. A C. tetradenius collection can be established in the Active Germplasm Bank of Medicinal and Aromatic Plants of the Federal University of Sergipe with the C. tetradenius plants collected. It is necessary to collect additional individuals in the four populations evaluated and to obtain samples from other regions where the species occurs to expand the genetic base. The formicidal activity of the essential oils and major compounds of C. tetradenius was confirmed, showing its potential as a natural insecticide against A. balzani.